2018
DOI: 10.1007/s11920-018-0905-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Borderline Personality Disorder in the College Mental Health Setting

Abstract: Preliminary studies of targeted treatment for BPD on college campuses are promising. They suggest that even pared-down interventions have the potential to help students feel better and function better. Experts in college mental health treatment emphasize the importance of gathering data, intervening early, communicating across treatment environments, appropriately marshaling resources, and providing psycho-education. To bring the on-campus treatment of BPD in line with best-practice guidelines, improved diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Affective instability is a key feature of BPD (Winter, 2016) and some researchers have suggested changing the name of BPD to emotional regulation disorder (Paris, 2018). Others believe that patients with BPD need to understand the interpersonal source of their emotional symptoms and learn to work on their relational issues (Brickell, 2018). Therapists should help the patients gain confidence in their emotion regulation measures as regular skill training improves emotional intelligence in BPD (Jahangard et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Affective instability is a key feature of BPD (Winter, 2016) and some researchers have suggested changing the name of BPD to emotional regulation disorder (Paris, 2018). Others believe that patients with BPD need to understand the interpersonal source of their emotional symptoms and learn to work on their relational issues (Brickell, 2018). Therapists should help the patients gain confidence in their emotion regulation measures as regular skill training improves emotional intelligence in BPD (Jahangard et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, in Klein et al's study, the per-protocol approach demonstrated a significant decline in BPD symptoms, therefore hinting that, if patients are better supported in using the program, effectiveness may be more convincing. Psychoeducation in patients with BPD has been proven to be helpful in a regular care setting, which might explain why the former study did not find any significant changes [40]. However, as both studies suggested, accessibility is often limited, and an internet-based intervention could be interesting for patients with limited access to care providers.…”
Section: About the Findingsmentioning
confidence: 95%
“…The attainment of post‐secondary education in late adolescence and early adulthood is one common adaptive undertaking that serves to prepare individuals for responsibilities of adulthood, establish careers which will provide for material necessities, and facilitate lasting peer and romantic relationships. Although there is a substantial lack of data concerning the impact of BPD on college student functioning (Brickell, 2018), individuals with BPD have been shown to obtain lower education levels overall and greater attrition in post‐secondary education (Meaney et al, 2016). Therefore, identifying borderline features in college‐age students may hold great significance for reducing functional impairment later in life.…”
Section: Introductionmentioning
confidence: 99%